Impact of age on haematological markers pre- and post-marathon running - Martin, T. G.; Pata, R. W.; D`Addario, Yuknis, L.; Kingston, R.; Feinn, R. (Journal of Sports Sciences, 2015)
This study investigated whether haematological markers differ between young and masters marathon participants, running at similar performance levels. Nine young (31.89 ± 4.96 years) and eight masters (63.13 ± 4.61 years) runners participated. At five time points (pre-race through 54 h post-race), a complete blood cell count, basic metabolic panel and creatine kinase (CK) isoenzyme panel were assessed. Race performance was standardised using the World Masters Association Age Grading Performance Tables. Total CK levels were elevated for all participants at all time points post-race (P < 0.001). The CK-isoenzyme MB% was elevated across groups at 6, 30 and 54 h post-race (P < 0.01, P < 0.01 and P < 0.05), with masters runners having a higher CK-MB% at 30 and 54 h (P < 0.05, P < 0.05). Total white blood cell and neutrophil counts were elevated through 6 h post-race (P < 0.001), with higher levels found in younger runners (P < 0.001). When considering all blood work, masters runners had a higher number of abnormal values at 6, 30 and 54 h post-race (P < 0.05, P < 0.01 and P < 0.05). In conclusion, masters runners demonstrated sustained CK-MB elevation, which may suggest greater cardiac stress. However, future studies using additional cardiac markers should be completed to confirm these findings. In addition, masters runners showed an increased number of laboratory values outside normal range, indicating the body`s reduced capacity to respond to marathon running.